Entre a luta e o direito : políticas públicas de inclusão escolar de pessoas com deficiência visual - Melo, Douglas Christian Ferrari de (2016)
The objective of this thesis is to analyse the implementation of public policies of Special Needs Education for visually impaired people on the Municipal school systems in Vila Velha, Cariacica, Serra, Vitória, between 2008 and 2013. Using Gramsci's integral state theory as theoretical referential, I expatiated about social rigths and public policies. In this respect, I defended the thesis that the education, as a right, the presence of this right in the legislation and the implementation of the public policies are steps of a process which is lived as playing field whose is not conquered without fights. So, the public policies are the third step of fight to materialization of a right. The starting point was the principle of the public policies do not happen in the same way in each state and city, considering its specific socioeconomic and historical realities. In general, for being inside a macro context, the municipal policies do not dislocate, largely, from those are nationally effected, in the state or in the metropolitan region. Thus, I applied the Comparative Studies in Education methodology, from the method of content analysis and from the perspective of the historical dialectical materialism. Therefore, about the public policies directed for this area, it was verified, firstly, the nonexistence of a visually impaired assistance policy in the municipal law of the surveyed cities. In almost all cases, it was restricted to applying tests visual acuity and to offering school books. Secondly, the comparative research in the selected cities demonstrated a certain precariousness on special education sectors, which is reflected on the precariousness of the legislation and of public policies implemented by them. In this way, the teams' formation not always leads into the account the public policies directed to the visually impaired people. Thirdly, when contrasting what will be epresented in this research about Especialized Educational Service (in portuguese is presented as AEE), the continued formations and the undertaken actions, it was possible to detected a naturalization of pedagogic practice, which was developed with those students. Those practices are crystallized, fossilized. It is as if did not exist other needs/demands to be worked on, other actions to be developed and, even these, did not need to be questioned, transformed, reconfigured. The fourth and last place, considering the building of a pedagogical project and/or the action plan to the visual impairment area, the research showed that the presence of a specific subcoordenation leveraged the guidance of public policies to the visual impairment area, as Vila Velha's case. The nonexistence of such subcoordenation did not make impracticable this guidance, however it hampered this targeting, as in the case of Cariacica, Serra and Vitória